Classic Telescopes A Guide to Collecting, Restoring, and Using Telescopes of Yesteryear - English, Neil.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Classic Telescopes explores the exciting world of telescopes past, as well as the possibilities involved in acquiring these instruments. What are classic telescopes? First, the book takes a look at the more traditional telescopes built by the great instrument makers of the eighteenth and nineteenth centuries and the dynastic houses founded by the likes of John Dollond, Alvan Clark, Thomas Cooke & Sons and Carl Zeiss, plus some lesser-known luminaries, including John Brashear, John Calver, and Henry Fitz. Instruments constructed from the 1950s until as recently as the early 1990s are now also considered 'classic.' There is thus a very active market for buying and selling these 'modern' classics. The author examines some of the most talked about instruments on the amateur Internet forums, including the Unitron refractors, the Questar 90, a classic 6-inch reflector, the RV-6; a 3-inch F/15 achromat by Fullerscopes; the time-honored AstroScan Richfield reflector; and many, many more. Classic telescopes are of interest to amateur astronomers for a variety of reasons. There are, of course, the dedicated collectors, but in addition many amateurs love classic telescopes for their nostalgia. These telescopes have a fit and feel quite unlike any contemporary telescope and perhaps a unique ability to reconnect the owner to a bygone age of craftsmanship. This book not only informs as to what's out there and how to acquire it but also provides a wonderful historical background on the evolution of telescopes in a world just beginning to recognize the treasures to be found in scanning the skies. Just reading about this world can help you feel a part of it, and if you decide to continue on with collecting, then this book can serve as an invaluable guide in your pursuit.
Preface: The Appeal of Yesteryear.-Chapter 1: The Dollond Century -- Chapter 2: A Yorkshireman Makes Good -- Chapter 3: Once Upon a Time in America -- Chapter 4: Zeiss is Nice -- Chapter 5: The Story of Broadhurst, Clarkson & Fuller -- Chapter 6: The 60mm Brigade -- Chapter 7: Classic Specula -- Chapter 8: The Age of Unitron -- Chapter 9: Die Zauberflöte -- Chapter 10: Pioneers of the New Glass -- Chaper 11: Classic Cats -- Chapter 12: Resurrecting the Master's Glass -- Chapter 13: The Antique Telescpe in the Twenty-First Century -- Epilogue: Sailing to Byzantium -- References and Bibliography -- Glossary -- Index.
Keywords: Physics; Observations, Astronomical; Astronomy -- Observations; Astronomy; Physics; Astronomy, Observations and Techniques; Popular Science in Astronomy; Electronic books